Effects of Occult Hypoperfusion on Local Circulation and Inflammation - An Analysis in a Standardized Polytrauma Model - Halvachizadeh, Sascha; Kalbas, Yannik; Teuben, Michel Paul Johan; Teuber, Henrik; Cesarovic, Nikola; Weisskopf, Miriam; Cinelli, Paolo; Pape, Hans-Christoph; Pfeifer, Roman (Frontiers in Immunology, 2022)
Introduction Occult hypoperfusion (OH) is defined as persistent lactic acidosis despite normalization of vital parameters following trauma. The aim of this study was to analyze the association of occult hypoperfusion with local circulation and inflammation of injured soft tissue in a porcine polytrauma model. Methods This experimental study was performed with male landrace pigs who suffered a standardized polytrauma, including a femoral fracture, blunt chest trauma, liver laceration and a mean arterial pressure (MAP) controlled hemorrhagic shock. One hour after induction of trauma, the animals were resuscitated with retrograde femoral nailing, liver packing and volume replacement. Animals were stratified into Group Norm (normalizing lactate levels after resuscitation) and Group occult hypoperfusion (OH) (persistent lactate levels above 2 mmol/l with normalizing vital parameters after resuscitation). Local circulation (oxygen saturation, hemoglobin amount, blood flow) was measured with optical sensors at the subcutaneous soft tissue at the fractured extremity as well as at the stomach and colon. Local inflammatory parameters (interleukin (IL) 6, 8, 10, and heat shock protein (HSP)) were analyzed in the subcutaneous tissue of the fractured extremity. Results Group Norm (n = 19) and Group OH (n = 5) were comparable in baseline vital and laboratory parameters. The shock severity and total amount of blood loss were comparable among Group Norm and Group OH. Following resuscitation Group OH had significantly lower local relative hemoglobin amount at the injured soft tissue of the fractured extremity when compared with Group Norm (39.4, SD 5.3 vs. 63.9, SD 27.6 A.U., p = 0.031). The local oxygenation was significantly lower in Group OH compared to Group Norm (60.4, SD 4.6 vs. 75.8, SD 12.8, p = 0.049). Local IL-6 in the fatty tissue was significantly higher in Group OH (318.3, SD 326.6 [pg/ml]) when compared with Group Norm (73.9,SD 96.3[pg/ml], p = 0.03). The local circulation at the abdominal organs was comparable in both groups. Conclusion OH is associated with decreased local circulation and increased local inflammation at the injured soft tissue of the extremity in polytrauma. OH might reflect the severity of local soft tissue injuries, and guide treatment strategies.